Olfactory cues of habitats facilitate learning about landscapes of fear. (5th April 2018) - Mitchell, Matthew D; Crane, Adam L; Bairos-Novak, Kevin R; Ferrari, Maud C O; Chivers, Douglas P
Abstract : As animals move through their environment, they must respond to different levels of predation risk in different habitats. We demonstrate that tadpoles use habitat odors to learn about the overall risk associated with specific habitats. Tadpoles adjusted their antipredator behavior to match the risk experienced in different habitats, becoming neophobic (fearful of novel odors) in high-risk habitats. However, responses were not consistent across habitat types, and tadpoles did not use habitat cues when learning about predators. Abstract: Across landscapes, prey are exposed to different levels of predation risk within different habitats. However, little is known about how prey learn about risk in different habitat types. Here, we examined if wood frog tadpoles, Lithobates sylvatica, use olfactory cues from 2 distinct, plant-dominated habitats (cattail and pond weed) to learn about the overall risk within a habitat and the risk posed by a specific predator species within different habitats. In our first experiment, tadpoles experienced both a high-risk and a low-risk habitat before being tested for habitat-specific neophobic responses, a cognitive trait expressed in high-risk but not low-risk environments. In the second experiment, we taught tadpoles to recognize a predator in one habitat while the other one was never associated with a predator. Tadpoles were then tested for their responses to the predator and a control in both habitats. Our results showed that high-risk cattail tadpoles developed habitat-specific neophobia. However, high-risk pond weed tadpoles developed a generalized neophobia, responding to the novel cues irrespective of the habitat where they were tested. We also found that the habitat in which prey learned the identity of a specific predator did not affect their responses to that predator when tested in different habitats. Our results provide support for the use of olfactory habitat cues by prey to learn about predation risk across landscapes, suggesting unrecognized nuances to how prey use such cues to learn about predation risk.